Rehabilitation following arthroscopic rotator cuff repair - Koo, S. S.; Burkhart, S. S. (Clinics in Sports Medicine, 2010)
The postoperative rehabilitation program is critical for the successful arthroscopic treatment of rotator cuff injury. The authors' experience has confirmed that the best clinical results (restoration of strength, motion, and relief of pain) following rotator cuff repair are achieved after a durable repair of tendon to bone that heals in its entirety. Therefore, the senior author (SSB) has adopted a customized rehabilitation protocol to optimize postoperative range of motion while maintaining rotator cuff integrity. A customized rehabilitation program that begins closed-chained overhead stretches (table slides) early for groups at risk for developing stiffness and delays overhead stretches for the remaining patients until 6 weeks is best to avoid stiffness without potentially increasing the risk of rerupture in the early postoperative period.